Singapore’s travel behaviour on various transport modes - Lee, Ee Ling (2020)
This research target to examine how travel behavior affects the transportation ecosystem in Singapore. Singapore as a densely populated city-state with only 719 square km and a population of 5.5 million often treated as an example of world-class urban transportation system with efficient public buses and Mass Rapid Transit (MRT) network systems. With the additional entrance of ride-hailing service into the Country few years ago, this study will focus on traveler’s characteristic and how these characteristics leads to the motivation that that influences the choice of different transport modes. Additionally, it will be reviewed if ride-hailing eventually affects public transportation and local taxis ridership in Singapore. At present, there are several quantitative studies conducted on travel behavior selecting various transport modes – ride-hailing and local transportation mainly in US or Europe context only. Hence, this study aims to address these gaps in Singapore context using qualitative method.